Commentary on Boshkoff, Some Gloomy Thoughts Concerning Cross-Border Insolvencies - Ian F. Fletcher (Washington University Law Quarterly, 1994)
The fruits of long experience suggest that caution and skepticism are essential qualities of mind with which to approach the phenomenon of cross-border insolvency and the multiple problems generated thereby. Pessimism may thus be acknowledged as closely akin to realism for the current purpose.
Keywords: Bankruptcy; International; United States; International bankruptcy